Circle of fortune: The long term impact of Western customs institutions in China - Gan Jin (University of Freiburg, Department of International Economic Policy (iep), 2018)
This paper studies the persistent impact of good institutions on economic development in China. By exploiting a British-driven institutional switch in part of China's customs stations in 1902, I find that counties that were more affected by the British customs institutions are also better developed today. Moreover, I show that the institutional switch was exogenous to the pre-colonial development, and I provide different estimation models to reveal a robust and causal relationship between good institutions and economic development.
Keywords: N15; O10; P51; 330; Institutions; Economic development; Treaty ports; Chinese Maritime Customs Service (CMCS); China